Towards a Political Economy of Charging Regimes: fines, Fees and Force in Uk Immigration Control - Burnett, Jon (The British journal of criminology, 2020)
Charging regimes and the extraction of revenue are integral components of immigration control in the United Kingdom. However, while these have been analysed in their individual guises, to date, there has been little substantive analysis bringing these regimes together and locating them at the centre of its enquiry. Drawing on data obtained through the Freedom of Information Act 2000, this paper consequently examines the functions of charging regimes as a distinct form of statecraft, focussing its attention on UK Visas and Immigration fees and charges, carrier sanctions, charges related to accessing services and civil penalties administered though immigration enforcement. Analysing their historical roots and their contemporary prevalence, it suggests that they contribute to the political economy of financial power, which has significant implications for understandings of criminalization and immigration enforcement.